Sago wastes and its applications - M. Amin, Nurhusni; Sabli, Nordin; Siajam, Shamsul Izhar; Yoshida, Hiroyuki (Universiti Putra Malaysia Press, 2019)
The sago starch industry is one of the major revenue sources of the Malaysian state of Sarawak. This state is currently among the world’s leading producers of sago starch, exporting more than 40,000 tons every year to different Asian countries. This number is expected to rise since starch production and export value have been increasing 15.0%-20.0% each year. Sago palm is subjected to various processes to obtain starch from its trunk. During processing, a huge amount of residual solid wastes is generated, such as bark and hampas, and in general, is burned or washed off to nearby streams. Along with the rising sago starch demand, the sago starch industry is now facing waste management problems, which have resulted in environmental pollution and health hazards. These wastes comprise starch, hemicellulose, cellulose, and lignin; hence, can be valorized into feedstock as value-added products. To date, these wastes have been utilized in the production of many materials like adsorbents, sugars, biofuels, nanomaterials, composites, and ceramics. This review article aims to summarize the various methods by which these wastes can be utilized besides to enlighten the major interest on sago hampas and bark.